Influence of modulus-to-hardness ratio and harmonic parameters on continuous stiffness measurement during nanoindentation. (1st August 2017) - Merle, Benoit; Maier-Kiener, Verena; Pharr, George M.
Abstract: Dynamic nanoindentation is a popular method for continuously probing the mechanical properties of a sample as a function of depth. It is shown here that special caution should be exercised when testing materials with high modulus-to-hardness ratios (E/H) at fast loading rates, as the choice of harmonic parameters can result in a significant underestimation of the contact stiffness and hence the elastic modulus. The origin of this behavior is traced back to a bias occurring during signal processing by the lock-in amplifier. The possible consequences of flawed measurements are highlighted and a practical method for detecting possible occurrence from the phase angle signal is presented. Graphical abstract: